ESTIMASI DAN UJI EKSAK KOMPONEN VARIANSI PADA MODEL RANDOM KLASIFIKASI DUA ARAH DENGAN DATA TIDAK SEIMBANG - Efendi, Rustam (Jurnal Pilar Sains, 2008)
This manuscript dicusses about the model equation yijk     i   j  ( ) ij  eijk ; i  1, 2,  , r ;whereis a constant andand variances i ,  j , ( ) ij , eijkj  1, 2,  , s ; k  1, 2,  , nij ; nij  1are distributed independently and normally with zero means2222  ,   ,   ,  e , respectively. From this model is given estimation and exact test of the itsvariance components.Key Words: Unbalanced Data, Variance Components, and Testing Hypothesis.